The clinical application and challenges of preimplantation genetic testing - Fan Zhou; Fan Zhou; Xinlian Chen; Xinlian Chen; Shanling Liu; Shanling Liu; Xiaodong Wang; Xiaodong Wang (Frontiers in Genetics)
Preimplantation genetic testing (PGT) has rapidly advanced due to the significant development of genetic testing technologies. As an integration of genetic testing and assisted reproductive technology (ART), PGT plays a pivotal role in the primary prevention of birth defects, mainly chromosomal abnormalities and monogenic disease with known pathogenic variants. Blastocyst biopsy entails the collection of a relatively higher number of cells compared to other methods. Thereafter, whole genome amplification (WGA) generates a substantially larger amount of DNA templates, enabling more accurate subsequent genetic analyses. As an evolving technique that continues to be improved, the inherent limitations of WGA are expected to be minimized in the near future. Despite the widespread application of genetic techniques to WGA products, challenges remain in the downstream detection of small-fragment copy number variations (CNVs) (particularly those <1 Mb), the inability of long-read sequencing to resolve haplotypes or determine the position and orientation of micro-duplications for specific genomic sequences. Additionally, identifying complex or cryptic structures of balanced chromosomal rearrangements in prospective parents with a history of adverse pregnancy outcomes represents an urgent and challenging task, which would facilitate the pre-testing evaluation of PGT indications. Meanwhile, further assessment of the risks associated with transferring embryos with mosaic chromosome abnormalities, the implantation potential of euploid embryos, as well as the long-term health outcomes of children born following PGT requires more rigorously designed studies to provide robust evidence. The technology of PGT will continue to evolve, becoming increasingly comprehensive and precise. However, this technology should be applied strictly in accordance with legislation and ethical guidelines, with the ultimate aim of benefiting couples.